1770
DOI: 10.5962/bhl.title.531
|View full text |Cite
|
Sign up to set email alerts
|

Hortus botanicus vindobonensis, seu, Plantarum rariorum, quae in Horto botanico vindobonensi ... :coluntur, icones coloratae et succinctae descriptiones

Abstract: Pl.inra^l iabitu coogcnemm* opud nos dimn f?rr non canriirn, fed vcl aliquotiej j:im in huTto c fructibu? rcfiitis negkflj^qoe fpome prodivjc, jMelonc vulgnri omnibus parci-bn^niinor^l o^a fiemrem fpnrgii naufcofimi, Caules & pcUoli font afperi atque iinguJoli. FdJa foot coidara , fubtus ofpersj quinquduba dcniaiaque ', lubo inccniKdio ferme di:plo A lull-lon^larl Podunculi aTiUhvi^^& iiiiinori liorcs gcriTiii dioraaeii Llnij^nno nmriiinodc con-grucjiEC^. FruQiis fiinc globofi, gbbd. aciifcis mnocuis moJiibu? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This grouping implies that the genus Sempervivum is not closely affiliated with the Macaronesian Sempervivoideae (Aeonium and Monanthes). A possible close relationship between Sedum series Rupestria, represented by S. sediforme in the present study, and Sempervivum has earlier been suggested by Jacquin (1770) and Uhl (1961b) on the basis of their polymerous flowers and accuminate leaves.…”
Section: Resultssupporting
confidence: 79%
“…This grouping implies that the genus Sempervivum is not closely affiliated with the Macaronesian Sempervivoideae (Aeonium and Monanthes). A possible close relationship between Sedum series Rupestria, represented by S. sediforme in the present study, and Sempervivum has earlier been suggested by Jacquin (1770) and Uhl (1961b) on the basis of their polymerous flowers and accuminate leaves.…”
Section: Resultssupporting
confidence: 79%
“…non Linn.”. Thus, Smith indicated that the herbarium specimen does not match the description of P. laurifolia by Linnaeus but corresponds to that of Jacquin (1776) in Hortus Vindobonensis where this author specifies that P. laurifolia has two series of filaments, the outer series being shorter. Below the first annotation, “ pallida ” can be read, hand-written by Linnaeus and next to that name, another annotation from Smith: “non Plumeri icon”).…”
Section: Resultsmentioning
confidence: 99%
“…■ VALID PUBLICATION OF ABROMA The name "Abroma" was first used by Jacquin (1776) when he published "Abroma fastuosum", with Theobroma augustum L. cited in synonymy. Later, Linnaeus filius (1782) described "Ambroma" and created "Ambroma augusta" (L.) L.f. with Theobroma augustum and "Abroma fastuosum" in synonymy.…”
mentioning
confidence: 99%
“…According to Fosberg (1966), "Abroma" was not validly published by Jacquin (1776) because he failed to provide a separate generic description or diagnosis. What is more, the description of the single species "Abroma fastuosum" could not be accepted as a combined genus/species description (descriptio generico-specifica), as the homotypic Theobroma augustum was cited in synonymy (ICN Art.…”
mentioning
confidence: 99%
See 1 more Smart Citation